Interactions of the Brain Renin-Angiotensin-System (RAS) and Inflammation in the Sensitization of Hypertension - Xue, Baojian; Zhang, Yuping; Johnson, Alan Kim (Frontiers in Neuroscience, 2020)
Mounting evidence indicates that the renin-angiotensin (RAS) and immune systems interact with one another in the central nervous system (CNS) and that they are importantly involved in the pathogenesis of hypertension. Components comprising the classic RAS were first identified in the periphery, and subsequently, similar factors were found to be generated de novo in many different organs including the brain. There is humoral-neural coupling between the systemic and brain RASs, which is important for controlling sympathetic tone and the release of endocrine factors that collectively determine blood pressure (BP). Similar to the interactions between the systemic and brain RASs is the communication between the peripheral and brain immune systems. Systemic inflammation activates the brain’s immune response. Importantly, the RAS and inflammatory factors act synergistically in brain regions involved in the regulation of BP. This review presents evidence of how such interactions between the brain RAS and central immune mechanisms contribute to the pathogenesis of hypertension. Emphasis focuses on the role of these interactions to induce neuroplastic changes in a central neural network resulting in hypertensive response sensitization (HTRS). Neuroplasticity and HTRS can be induced by challenges (stressors) presented earlier in life such as a low-dose of angiotensin II or high fat diet (HFD) feeding in adults. Similarly, the offspring of mothers with gestational hypertension or of mothers ingesting a HFD during pregnancy are reprogrammed and manifest HTRS when exposed to new stressors as adults. Consideration of the actions and interactions of the brain RAS and inflammatory mediators in the context of the induction and expression of HTRS will provide insights into the etiology of high BP that may lead to new strategies for the prevention and treatment of hypertension.